DRP1 interacts directly with BAX to induce its activation and apoptosis. (13th January 2022) - Jenner, Andreas; Peña‐Blanco, Aida; Salvador‐Gallego, Raquel; Ugarte‐Uribe, Begoña; Zollo, Cristiana; Ganief, Tariq; Bierlmeier, Jan; Mund, Markus; Lee, Jason E; Ries, Jonas; Schwarzer, Dirk; Macek, Boris; et al.
Abstract: The apoptotic executioner protein BAX and the dynamin‐like protein DRP1 co‐localize at mitochondria during apoptosis to mediate mitochondrial permeabilization and fragmentation. However, the molecular basis and functional consequences of this interplay remain unknown. Here, we show that BAX and DRP1 physically interact, and that this interaction is enhanced during apoptosis. Complex formation between BAX and DRP1 occurs exclusively in the membrane environment and requires the BAX N‐terminal region, but also involves several other BAX surfaces. Furthermore, the association between BAX and DRP1 enhances the membrane activity of both proteins. Forced dimerization of BAX and DRP1 triggers their activation and translocation to mitochondria, where they induce mitochondrial remodeling and permeabilization to cause apoptosis even in the absence of apoptotic triggers. Based on this, we propose that DRP1 can promote apoptosis by acting as noncanonical direct activator of BAX through physical contacts with its N‐terminal region. Synopsis: Apoptotic executioner BAX and dynamin‐like protein DRP1 colocalize at mitochondria during apoptosis, but their interplay in mediating mitochondrial permeabilization and fragmentation remains incompletely understood. Here, DRP1 is found as direct interactor and noncanonical activator of BAX promoting apoptosis. BAX and DRP1 interact directly and their association is enhanced during apoptosis. BAX/DRP1 interaction takes place in the membrane environment and requires the N‐terminal region of BAX. BAX and DRP1 mutually enhance each other's membrane remodeling activity. Forced dimerization of BAX and DRP1 triggers their translocation to mitochondria and induces apoptosis in the absence of apoptotic triggers. Abstract : Dynamin‐like protein DRP1 can promote apoptosis by inducing activation and mitochondrial translocation of apoptotic executioner protein BAX.